Modeling the emergence flow of Conyza bonariensis "Rama Negra": (Ingeniería Agronómica) (Semiárida, 2022)
Conyza bonariensis is a ruderal species that occurs in much of the agricultural area of the country and the world. In Argentina, around 23 species have been classified, of which in the semi-arid and subhumid Pampas region it is common to find two varieties: Conyza bonariensis var. bonariesis and var. angustifolia. The general objective of the following work was to adjust humidity and temperature parameters to the Hydrothermal Model for said species in the Semiarid Pampas Region. The sampling sites were set at the INTA Anguil Experimental Station and at the La Armonía establishment. Seedling sampling was carried out in fixed microplots of 0.25 m² (n: 12; N: 24) approximately every 10 days during the species' growing season. The Soil Temperature and Moisture Model (STM2) was used, which simulates water dynamics and soil temperature. To predict seedling emergence patterns, cumulative percent emergence values were compared to the hydrothermal times used with the Weibull function. An independent data set was used to validate the model. To determine the degree of fit between the predicted and observed emergence, the square root of the mean square error (RMSE) was used. The cumulative emergence of black branch seedlings presented an increasing number of individuals. The emergence flow occurred mainly in autumn and spring. The model presented an adequate fit. The equation obtained allowed us to describe the expected behavior of this weed in the local-regional context. The accumulated hydrothermal time of the first emergence (z) is a useful parameter as an early warning. Starting from the estimated value of 600, it would indicate that the humidity and temperature conditions are in place for the beginning of weed emergence in the area.Director: Suárez, Carla EtelCo-Director: Montoya, Jorgelina Ceferina
Keywords: conyza bonariensis